Heidegger’s Interpretation on Nietzsche’s Concept of Nihilism - Labanukrom, Naruedej (Journal of Liberal Arts Prince of Songkla University, 2016)
Nietzsche views our ‘modernity’ as leading towards the kind of crisis – a loss of meaning and value: today we are currently witnessing the collapse of prior truths and values. Much has been discussed concerning the relevance of Nietzsche’s concept of nihilism. As one of Heidegger and Nietzsche’ readers, I want to reveal and investigate in this paper how Heidegger further enhanced Nietzsche’s concept of nihilism, especially relative to ‘revaluation’ of value, Being and historicity. In addition, this paper also insists upon the notion that the apriority does not involve necessity since all a priori propositions need not be necessarily true. The paper has been separated into four sections in order to not only enrich the quintessence of nihilism that steer the primacy of research, but also urge the readers to view nihilism not as a complete negative downfall, but on the contrary, as the positive transition to new conditions of human existence according to both Heidegger and Nietzsche.